Stabilization of 6H-Hexagonal SrMnO3 Polymorph by Al2O3 insertion. Issue 10 (August 2021) - Sheeraz, Muhammad; Rashid, Mamoon Ur; Ali, Asad; Akram, Fazli; Lee, Ho Jeong; Choi, Jin San; Bae, Jong-Seong; Kim, Yong Soo; Shin, Young-Han; Ahn, Chang Won; Kim, Tae Heon
Abstract: We demonstrate the structural evolution of polymorphic phases in Al2 O3 -inserted SrMnO3 ceramics synthesized by solid state reaction. While the 4H-hexagonal phase is predominant in pure SrMnO3 ceramics, a small amount of 6H-hexagonal polymorph is identified in addition to the primary 4H-hexagonal SrMnO3 and the secondary hexagonal SrAl2 O4 phases in the as-sintered ceramics, evidenced by x-ray diffraction and subsequent Rietveld refinement analyses. The existence of the 6H-hexagonal SrMnO3 phase is corroborated using Raman spectroscopy. The chemical compositions and electronic structures of the Al2 O3 -inserted SrMnO3 compounds are also examined using energy dispersive spectroscopy and x-ray photoelectron spectroscopy, respectively. The first-principles calculations reveal that there is no clear difference between the total energies of 4H- and 6H-hexagonal polymorphs regardless of the presence/absence of Sr and oxygen vacancies. Possible origins are discussed with the estimation of actual strain based on the refined lattice parameter of 6H SrMnO3 .